2016
DOI: 10.1097/aog.0000000000001681
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes With Cerclage Alone Compared With Cerclage Plus 17α-Hydroxyprogesterone Caproate

Abstract: Women receiving transvaginal cerclage plus 17α-hydroxyprogesterone caproate had a 69% relative reduction in delivery at less than 24 weeks of gestation when compared with women receiving cerclage alone. We found no difference in overall preterm delivery or preterm PROM. In this cohort, compared with cerclage alone, the likelihood of a viable neonate improves with both treatments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 11 publications
2
17
1
2
Order By: Relevance
“…In addition, health insurance companies continually refused to issue prior authorizations to commence 17‐OHPC as adjunctive therapy in women with a history‐indicated cerclage, asserting that it remains investigational in this setting and is not supported by available data . One recent retrospective cohort study reported that combination therapy (cerclage+17‐OHPC) was more effective than cerclage alone for preventing spontaneous preterm birth at less than 24 weeks, but not at less than 28 or 37 weeks of gestation . However, the small number of spontaneous preterm births <24 weeks in this study precludes a clear conclusion about the efficacy of combined therapy.…”
Section: Introductioncontrasting
confidence: 56%
See 4 more Smart Citations
“…In addition, health insurance companies continually refused to issue prior authorizations to commence 17‐OHPC as adjunctive therapy in women with a history‐indicated cerclage, asserting that it remains investigational in this setting and is not supported by available data . One recent retrospective cohort study reported that combination therapy (cerclage+17‐OHPC) was more effective than cerclage alone for preventing spontaneous preterm birth at less than 24 weeks, but not at less than 28 or 37 weeks of gestation . However, the small number of spontaneous preterm births <24 weeks in this study precludes a clear conclusion about the efficacy of combined therapy.…”
Section: Introductioncontrasting
confidence: 56%
“…Four of the studies were retrospective cohort studies and one was a randomized trial . Four of the studies were carried out in the USA and one was done in Israel . Two of the studies were published in 2018, in 2016, in 2014 and one in 1985 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations